1998
DOI: 10.1021/tx980087q
|View full text |Cite
|
Sign up to set email alerts
|

Additional Pathways of S-Conjugate Formation during Interaction of 4-Nitrosophenetole with Glutathione

Abstract: The rapid reactions of nitrosoarenes with cellular SH groups have proved to be main metabolic conversions during detoxication. Interactions of the phenacetin metabolite 4-nitrosophenetole with glutathione have been investigated in detail during the last years, revealing a complex pattern of products depending on the stoichiometry of the reactants and reaction conditions. Eight metabolites have been identified hitherto, and the present work extends this medley by six additional products. Three metastable sulfen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Several synthetic routes to sulfenamides have been developed over the years; however, information on the enzyme-catalyzed formation of these derivatives is relatively sparse. Mulder et al (1984) and Gallemann et al (1998) have previously reported the formation of a sulfenamide derivative of GSH. This conjugate was formed by reaction of 4-nitrosophenetole, derived from the oxidative metabolism of phenacetin via N-hydroxy-p-phenetidine, and GSH (Mulder et al, 1984;Gallemann et al, 1998).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several synthetic routes to sulfenamides have been developed over the years; however, information on the enzyme-catalyzed formation of these derivatives is relatively sparse. Mulder et al (1984) and Gallemann et al (1998) have previously reported the formation of a sulfenamide derivative of GSH. This conjugate was formed by reaction of 4-nitrosophenetole, derived from the oxidative metabolism of phenacetin via N-hydroxy-p-phenetidine, and GSH (Mulder et al, 1984;Gallemann et al, 1998).…”
Section: Discussionmentioning
confidence: 97%
“…Mulder et al (1984) and Gallemann et al (1998) have previously reported the formation of a sulfenamide derivative of GSH. This conjugate was formed by reaction of 4-nitrosophenetole, derived from the oxidative metabolism of phenacetin via N-hydroxy-p-phenetidine, and GSH (Mulder et al, 1984;Gallemann et al, 1998). However, the formation of N-acylsulfenamide, similar to the one described in this report, is not known.…”
Section: Discussionmentioning
confidence: 97%
“…GSO-NHPt: m / z 459 (100%, [M+H] + ), 322 (45%, [GSO] + ). GS-NHPt: m / z 443 (100%, [M+H] + ), 306 (37%, [GS] + ) ( , ). The presumed Et/Me-ketal eluting immediately in front of the sulfenamide GS-NHPt (Figure b) was detected by its UV absorption at 340 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The scarce results reported hitherto on the reactivity of sulfenamide cations indicate the ring positions to react primarily with soft nucleophiles ( , ). The only reaction with a hard nucleophile, solvent water, is reported in the preceding paper ().…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation